Development of black-grass (Alopecurus myosuroides) in regard to different herbicide systems and soil management treatments - Gehring, Klaus; Thyssen, Stefan; Festner, Thomas (Julius-Kühn-Archiv, 2016)
In 2011, a long-term field trial started in a winter wheat monoculture at Pettenbrunn, north of Freising, to examine the population and resistance dynamic of black-grass (Alopecurus myosuroides). Four different herbicide regimes and two different tillage methods were used as test factors. The two tillage methods were differentiated by a ploughing vs. non-ploughing primary soil tillage treatment. For the purpose of surveying of black-grass, the density of black-grass plants and seed heads in the treatment areas and in untreated control plots was assessed. In addition, a biotest to examine the herbicide resistance status was carried out using seed samples from untreated control areas. The results of the plant density survey and the resistance examinations are presented for the experiment period 2011 to 2015 and evaluated statistically on the basis of a ranking analysis. With regard to the development of the plant density of black-grass, the type of tillage had a significant influence. The herbicide regimes tested had a significant influence only on the number of seed heads in the treated area. In the factor combination, the method of tillage caused significant differences in plant density. In addition, there were also differences between the herbicide regimes within the non-ploughed plots. The resistance examinations showed a significant influence of the tillage method, while no differentiation emerged between the herbicide regimes. Specific differentiation occurred in the factor combination of tillage and herbicide regime. For the herbicides tested for resistance, significant differentiation occurred between the individual active ingredients and mode of action groups. The results show a development of the population dynamic and herbicide resistance in connection with the test factors, which are obviously not concluded and which must be further examined.